The Wittenoom Legacy - Musk, A.; Reid, A.; Olsen, N.; Hobbs, M.; Armstrong, B.; Franklin, P.; Hui, J.; Layman, L.; Brims, Fraser; Alfonso, H.; Shilkin, K.; Sodhi-Berry, N.; et al. (WILEY, 2018)
Introduction/Aim: In the fifty years since the Wittenoom crocidolite (blue asbestos) industry ceased operating, the epidemic of asbestos‐related diseases in Australia has intensified. Use of the employment records of the Australian Blue Asbestos Company and records of the Wittenoom township residents has permitted two cohorts of people with virtually exclusive exposure to blue asbestos to be assembled. Methods: Exposure data have been analysed and follow‐up of these two cohorts has been conducted through all available public records including mortality records in all states of Australia and in Italy, cancer registries of Western Australia (WA) and Federal mesothelioma registries. Results: Although the pattern of occurrence of asbestos‐related diseases in the Wittenoom cohorts has changed, there has been an ongoing epidemic of mortality from lung cancer and malignant mesothelioma and also from asbestosis. Benign pleural diseases continue to be seen. Quantitative exposure‐response relationships have been established. Conclusion: The industrial disaster that was Wittenoom has been directly responsible for many deaths as well as ongoing disease and social issues in people who worked in the mine and mill, who lived in the town, were involved in the transport of asbestos or were exposed to the product occupationally, domestically or environmentally subsequently. The legacy continues. It has prompted the establishment of epidemiological, clinical and scientific research groups in order to understand the biology and behaviour of the various asbestos‐related diseases and improve their diagnosis and clinical management, thereby contributing significantly to scientific knowledge.